Sterile inflammation, cross-presentation, autophagy and adaptive immunity in immunoinflammatory rheumatic diseases - M. Z. Saidov (Медицинская иммунология, 2024)
Proinflammatory extracellular and intracellular DAMPs are the dominant etiological factors of sterile inflammation in immuno-inflammatory rheumatic diseases. They are generated by systemic progressive disorganization of loose fibrous unformed connective tissue, programmed cell death and cell necrosis. Sterile inflammation is a multi-stage process which is induced by a sequence of reactions mediated by leukocytes and resident cells of the macrophage-monocyte series, aimed at cleansing the focus of inflammation from cellular and tissue detritus, followed by restoration of homeostasis of damaged tissue. An important role in this process belongs to the transendothelial migration of leukocytes to the focus of sterile inflammation and formation of cellular inflammatory infiltrate. The key feature of these events is the reactivity of PRR receptors followed by a cascade of PRR-DAMPs interactions with subsequent launch of molecular and cellular processes causing the local and/or systemic manifestations of sterile inflammation. Activation of innate immunity is the result of PRR-DAMPs interactions which launches the molecular and cellular reactions. Hence, it is possible to attribute the immunoinflammatory rheumatic diseases to the category of systemic sterile autoinflammatory processes. Generalization of the pathophysiological effects of pro-inflammatory DAMPs and, accordingly, the systemic and multi-organ nature of tissue and internal organ damage in immunoinflammatory rheumatic diseases is due to the wide occurrence of receptors for “danger signals”. The most important place in the development of DAMP-mediated sterile inflammation is occupied by the phenomenon of cross-presentation and autophagy. The cross-presentation causes exposition of extracellular DAMPs from internalized proteins with MHC class I molecules to autoreactive CD8+ cytotoxic T lymphocytes. Autophagy provides processsing of intracellular peptide DAMPs, their loading onto MHC class II molecules with subsequent induction of adaptive immune response in CD4+T cell populations. The innate lymphoid cells (ILC) make an important contribution to these processes. The model of functional coupling and complementarity between ILCs and Th-CD4+T cells has expanded our understanding of immune regulation by extending the activity of innate and adaptive immunity to the level of maintaining tissue homeostasis, morphogenesis, repair, regeneration and inflammation. Progression of systemic sterile inflammation may be a result of PRR-DAMP interactions of tissue ILCs followed by switching of ILC/Th-CD4+T cell partners. The data presented in this review define the promising molecular and cellular targets aiming for regulation and/or inhibition of sterile inflammation in immunoinflammatory rheumatic diseases.